A hybrid control method to suppress the three time fundamental frequency neutral-point voltage fluctuation in a VIENNA rectifier - Song, Wei-Zhang; Xing, Fei-Xiong; Yang, Hua; Empringham, Lee; De Lillo, Liliana; Wheeler, Patrick; Li, Jie; Zhong, Yan-Ru (IEEE, 2015)
This paper presents a solution to the control of the three times fundamental frequency fluctuation of the neutral-point in a VIENNA rectifier. A hybrid method combining a dynamic adjustment factor with a voltage deviation control of the split DC-link is proposed. The fluctuation of the neutral-point has been analyzed and the reason for the three times fundamental frequency fluctuation has been described using a mathematic model. As well as minimizing the three times fundamental frequency component in the neutral-point voltage the proposed control method also provides immunity to the influence of changes in the capacitor voltage. Furthermore, significant fluctuation in the neutral-point voltage caused by asymmetric capacitor parameters or unbalanced load can be effectively reduced by using a hybrid control method combining additional adjustment coefficients. The feasibility and effectiveness of the proposed strategy has been verified through the presented simulation and experimental results.